2000
DOI: 10.1002/clc.4960230103
|View full text |Cite
|
Sign up to set email alerts
|

Methods used to interpret the 12‐lead electrocardiogram: Pattern memorization versus the use of vector concepts

Abstract: Summary: This article extols the value of using Grant's approach to the interpretation of electrocardiograms (ECGs). The essay includes a discussion on how people learn and emphasizes the difference in memorizing information, thinking, and learning. Simply stated, the brains of most people are not designed to memorize countless numbers of ECG patterns. Accordingly, the essay supports the view that a method of interpretation must be used, and the reader is encouraged to use basic principles of electrocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 8 publications
0
34
0
1
Order By: Relevance
“…The assessment of ECG competency using nondigital examinations is hindered by the labor‐intensive effort in administering the examinations, which require manual review of each individual examinee's accompanying diagnosis for a particular ECG. This appears to have limited this area of education research to one or two‐center cohorts, as well as precluding the ability to conduct large‐scale workshops on ECG interpretation at any of the major national and international cardiology meetings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of ECG competency using nondigital examinations is hindered by the labor‐intensive effort in administering the examinations, which require manual review of each individual examinee's accompanying diagnosis for a particular ECG. This appears to have limited this area of education research to one or two‐center cohorts, as well as precluding the ability to conduct large‐scale workshops on ECG interpretation at any of the major national and international cardiology meetings.…”
Section: Discussionmentioning
confidence: 99%
“…This study further supports the concept that an inductive‐deductive reasoning strategy may be a more accurate approach to ECG interpretation, which may have important implications for medical education in how to teach ECG interpretation. The traditional method involves memorizing the patterns of ECGs and associating them with disease processes, but this is prone to error, whereas a patient's clinical history significantly improves a physician's diagnostic accuracy when reading ECGs . The concerning lack of trainee proficiency, combined with a lack of educational research examining the most accurate method for ECG interpretation, has left academic institutions without guidance in how to teach ECG interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, there are several recently-published articles regarding the best methods for educating medical students about the interpretation of electrocardiograms (ECGs) [22][23][24]. Whilst the ECG is a basic test for the diagnosis of acute coronary syndromes and myocardial infarction, it is not very useful for the diagnosis of coronary artery disease in the general population and is no longer recommended as a routine screening test for adults.…”
mentioning
confidence: 99%
“…Education on ECG interpretation provides a pertinent example of how to teach medical students to interpret the results of an important office-based test. Hurst [23] suggested that wave-form pattern recognition is an excellent initial approach to ECG education. Spirometry lends itself well to a similar approach because the flow-volume loops or expiratory curves can also be interpreted on the basis of a wave-form method.…”
mentioning
confidence: 99%